2020
DOI: 10.1038/s41598-020-65223-6
|View full text |Cite
|
Sign up to set email alerts
|

Using an Innovation Arena to compare wild-caught and laboratory Goffin’s cockatoos

Abstract: The ability to innovate, i.e., to exhibit new or modified learned behaviours, can facilitate adaptation to environmental changes or exploiting novel resources. We hereby introduce a comparative approach for studying innovation rate, the ‘Innovation Arena’ (IA), featuring the simultaneous presentation of 20 interchangeable tasks, which subjects encounter repeatedly. The new design allows for the experimental study of innovation per time unit and for uncovering group-specific problem-solving abilities – an impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 72 publications
1
43
0
Order By: Relevance
“…This higher motivation to manipulate and explore the apparatus could explain why they were more successful at innovating the use of the rope as a tool in this task. Recent findings from avian cognition have shown that Goffin's cockatoos (Cacatua goffiniana) that were temporarily held captive were less motivated to interact with a problem-solving task than those birds that had been hand-raised and lived longer in captivity (Rössler et al, 2020). Together with our study, such results suggest that captivity and human exposure may influence the motivational level rather than the animals' cognitive capacity per se.…”
Section: Problem-solving Differences Between Captive Facilitiessupporting
confidence: 72%
“…This higher motivation to manipulate and explore the apparatus could explain why they were more successful at innovating the use of the rope as a tool in this task. Recent findings from avian cognition have shown that Goffin's cockatoos (Cacatua goffiniana) that were temporarily held captive were less motivated to interact with a problem-solving task than those birds that had been hand-raised and lived longer in captivity (Rössler et al, 2020). Together with our study, such results suggest that captivity and human exposure may influence the motivational level rather than the animals' cognitive capacity per se.…”
Section: Problem-solving Differences Between Captive Facilitiessupporting
confidence: 72%
“…Crabbe et al, 1999;Many Primates et al, 2019), but also by using multiple different experimenters and varying the conditions and treatments within sites (Baribault et al, 2018;Richter et al, 2010;Wurbel, 2002). For example, Rössler et al, (2020) compared the ability of a sample of wild-caught Goffin's cockatoos and a sample of laboratory-housed Goffin's cockatoos to physically manipulate an apparatus to access a reward. However, rather than presenting the cockatoos with a single apparatus, they were tested in an area with a total of 20 apparatuses.…”
Section: Increasing Heterogeneitymentioning
confidence: 99%
“…Researchers also argue that captive subjects can perhaps re-direct resources (energetic or cognitive) no longer required for foraging or avoiding predation to perform the task (reviewed in Benson-Amram et al, 2013), or that in the field dominant subjects may prevent subordinates from accessing the apparatus for the amount of time necessary for devising a solution (Gajdon et al, 2004). Rössler et al (2020) argue instead that the observed behavioral differences, at least for Goffin's cockatoos (Cacatua goffiniana), are only in motivationthat captive subjects may, for example, simply interact more readily with the apparatus for reasons related to boredom, play, or from expectancies of rewards based on prior experience (see also Smith, Greene, Hartsfield, & Pepperberg, 2021). Rössler et al (2020) show compelling evidence that for their subjects that…”
mentioning
confidence: 99%
“…Rössler et al (2020) argue instead that the observed behavioral differences, at least for Goffin's cockatoos (Cacatua goffiniana), are only in motivationthat captive subjects may, for example, simply interact more readily with the apparatus for reasons related to boredom, play, or from expectancies of rewards based on prior experience (see also Smith, Greene, Hartsfield, & Pepperberg, 2021). Rössler et al (2020) show compelling evidence that for their subjects that…”
mentioning
confidence: 99%
See 1 more Smart Citation